ASSOCIATION BETWEEN MOTIVATION AND PROBLEM-SOLVING ABILITY: A REVIEW OF LITERATURE AND CORRELATIONAL META-ANALYSIS - Azizul Ghofar Candra Wicaksono; Ismi Nurul Qomariyah (JPPIPA (Jurnal Penelitian Pendidikan IPA), 2026)
This study was aimed at providing quantitative analysis of correlation between motivation and problem-solving ability. We conducted a systematic review from several published studies from 2000 to 2025. The studies collected in this review were selected from comprehensive search through databases including Google scholar, Science Direct, ERIC, and Research Gate. There are some inclusion criteria for literature selection including the using standardized problem-solving test and motivation questionnaire, and the availability of reported correlation coefficients. A total of 23 studies with 56 different samples were gathered in this review. The study showed that the average correlation from the studies showed low coefficient (r = .155, z = .157). The majority of studies used self-regulation, self-efficacy, intrinsic, and extrinsic motivation for measuring motivation level of students. Complex problem solving (CPS) was the most used test for assessing problem solving. A higher correlation between motivation and problem-solving ability was seen in the middle school level but shows similar trend over the educational level. Findings from the analysis imply that motivational factors will support problem solving in indirect ways. It gives challenge of instructional design to improve problem solving ability with integration of motivational factors.